Tracing Sources and Pathways of Trace Elements in Polar Regions by Isotopic Analysis - VECCHIO, MARIA ALESSIA (Università degli studi di Genova, 2025)
This PhD thesis focuses on the development, optimization and validation of robust analytical methods for accurate and precise isotopic analysis of Pb, Sr, Hg and Cd and their subsequent environmental application in extreme environments such as Antarctica and the Arctic. This work has been carried out in the contex of the National Antarctic Research Programme (PNRA). The primary objective is to trace the sources of heavy metals and assess their environmental impact using advanced inductively coupled plasma mass spectrometry (ICP-MS) techniques. The thesis is organized into eleven chapters as follows. The first chapter of this PhD thesis provides a description of the importance of Pb, Sr, Hg, and Cd, with a focus on their environmental applications. This includes a summary of their chemical characteristics, most common sources, toxicity, exposure pathways, health implications, and a general overview of their complex biogeochemical cycles. In addition, the capabilities of high-precision isotopic analysis as a means to study the occurrence of these heavy metals in the Antarctic and Arctic environment and a general overview of the their isotopic signatures reported for several environmental matrices, are provided. Chapter 2 summarizes the basic operating principles of ICP-MS, the technique of choice for isotopic analysis. In this chapter, the setup used during this PhD, comprising a cold-vapor generation (CVG) system for Hg introduction, an Aridus II desolvating system, single- and multi-collector ICP-MS instruments, are briefly described. Finally, the last part of this chapter is devoted to instrumental mass discrimination, a phenomenon strongly affecting MC-ICP-MS measurement results. This section discusses the origin of instrumental mass discrimination, the most widely applied approaches used for mass bias correction within the scientific community, and a more in-depth description of the correction approach selected in this PhD research project for Hg isotopic analysis. Chapter 3 investigates the biogeochemical ...